Epidemiology and predictors of multidrug-resistant Enterobacteriaceae in intensive care units of a tertiary hospital in Somalia: a five-year retrospective study (2019–2024) - Omar Sidow Zubair; Yusuf Hared Abdi; Tigad Abdisad Ali; Zakaria Ibrahim Issack; Abdirahman Abdirizak Ahmed (Frontiers in Antibiotics, 2026)
Background Multidrug-resistant Enterobacteriaceae (MDRE) represent a critical threat in intensive care units, particularly in low- and middle-income countries, where surveillance data remain scarce. This study characterized the epidemiology and predictors of multidrug resistance among Enterobacteriaceae isolates in a Somali tertiary hospital. Methods This retrospective descriptive study analyzed 758 unique Enterobacteriaceae isolates from culture-positive specimens between January 2019 and December 2024, using disk diffusion for eight agents; For colistin, broth microdilution (CLSI M07) was applied to isolates screening non-susceptible on disk diffusion, and genera with intrinsic polymyxin resistance ( Proteus , Serratia , Morganella ) were excluded from the colistin denominator. Multidrug resistance (MDR) was defined as nonsusceptibility to ≥3 antimicrobial classes. Bivariate associations and multivariable logistic regression identified the independent predictors of MDR. Results The overall prevalence of multidrug resistance was 37.9%. Klebsiella spp. demonstrated the highest MDR prevalence (54.9%), while Escherichia coli had lower odds of resistance (aOR, 0.27; 95% CI 0.19–0.38). Sputum specimens harbored the highest proportion of MDR isolates (44.9%), followed by blood (35.8%) and urine (19.0%). The prevalence of MDR remained relatively stable at 24–25% in 2019–2020, subsequently declined to 15% in 2021, and then escalated dramatically. Colistin retained the greatest in vitro activity: acquired resistance was documented in 1.2% (9/735 tested) of isolates from genera without intrinsic polymyxin resistance, all of them multidrug-resistant (9/283, 3.2%, versus 0/452 of non-MDR isolates; p = 0.001). A further 21/758 isolates (2.8%) belonged to genera intrinsically resistant to colistin. Because confirmatory broth microdilution was applied only to isolates screening non-susceptible, the colistin figure is a conservative lower-bound estimate. Tigecycline was tested in only 20.4% of isolates, among which resistance was 17.4%. Conclusions Multidrug-resistant Enterobacteriaceae are escalating alarmingly in Somali ICUs, with ciprofloxacin resistance of 95.4% among tested MDR isolates, which severely constrains empiric therapeutic options. The urgent implementation of antimicrobial stewardship programs, restricted-use protocols for carbapenems and colistins, and strengthened infection prevention measures are essential. National engagement with the WHO GLASS surveillance is critical.